Enhancing Asthma Patients' Self-Management through Smartphone-Based Application: Design, Usability Evaluation, and Educational Intervention - Farzandipour, Mehrdad; Nabovati, Ehsan; Heidarzadeh Arani, Marzieh; Akbari, Hossein; Sharif, Reihane; Anvari, Shima (Applied Clinical Informatics, 2019)
Objective The aim of this study was to design and evaluate a smartphone-based application for improving self-management in patients with asthma and evaluate its effects on their knowledge.Methods In this applied research, based on the Clinical Practice Guideline and a systematic review, a questionnaire was designed to determine the application information content and functionality requirements by 15 pediatric and adult asthma and allergy specialist. Then the application was designed and developed using Adobe Air software on the Android operating system. Usability evaluation of the mobile application was performed using the standard questionnaire for user interaction satisfaction (QUIS), which completed by 30 patients with asthma, 8 information technology (IT) specialists, and 2 asthma and allergy specialists. Self-management knowledge of 30 asthma patients was measured using a researcher-made questionnaire before and after using the application.Results The number of specialists in the both Delphi rounds was 15 and the mean work experiences were 17.6 years. The most important elements for asthma self-management were avoiding exposure to allergen and triggers (96%), drug treatment (94.6%), and how to use the therapeutic tools (92.4%), and the most important functionalities were alerting the patients when they did not control asthma (92%), setting reminders for timely drug use (85.4%) and therapeutic tools (82.6%), recording prescription drugs (82.6%), and peak flow meter values (82%). Usability evaluation showed that 30 patients with asthma, 8 IT specialists, and 2 physicians evaluated the application at a “good” level. The mean score of the patients' knowledge before intervention was 2.43 ± 0.95 which after intervention was significantly increased to 4.3 ± 0.56 (p < 0.001).Conclusion Considering the desirable outcomes of application evaluation and a positive impact of this educational intervention on asthma patients' knowledge, it is possible to use mobile-based self-management programs to help these patients to manage illness and gain knowledge and self-management skills.
Keywords: smartphone; application; usability; knowledge; asthma